Gallic acid protects against cyclophosphamide-induced toxicity in testis and epididymis of rats (2015)
The protective role of gallic acid (GA) on reproductive toxicity induced by cyclophosphamide (CPA), an antineoplastic drug, was investigated in male Wistar rats. Sixty rats were grouped into 10 rats per group. Group 1 (control) received distilled water. Rats in groups 2 and 3 received GA alone at 60 and 120 mg kg _1 for 14 consecutive days, respectively. Group 4 received a single intraperitoneal dose of CPA at 200 mg kg _1 on day 1. Groups 5 and 6 received a single dose of CPA (200 mg kg _1) intraperitoneally on day 1 followed by treatment with GA at 60 and 120 mg kg _1 for 14 consecutive days, respectively. In testes and epididymis of the treated rats, CPA administration resulted in significant elevation (P < 0.05) in malondialdehyde (MDA), nitrite and hydrogen peroxide levels. There was a significant decrease in the activities of superoxide dismutase and glutathione-S-transferase. Furthermore, there were significant reductions in plasma luteinising hormone (LH), follicle stimulation hormone (FSH) and testosterone levels, which were accompanied by significant decrease in sperm motility and viability in CPA-treated rats. Histological examination revealed marked testicular and epididymal atrophy in CPA alone treated rats and these aberrations were reversed by GA. In conclusion, GA has capacity to protect against reproductive toxicity induced by cyclophosphamide.